2018
DOI: 10.1111/jgh.14086
|View full text |Cite
|
Sign up to set email alerts
|

Linaclotide in irritable bowel syndrome with constipation: A Phase 3 randomized trial in China and other regions

Abstract: Once-daily 290-μg linaclotide improved bowel habits, abdominal symptoms, and global measures in a predominantly Chinese IBS-C population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 23 publications
5
65
0
Order By: Relevance
“…It is of interest that North America approved a lower dose of linaclotide for constipated patients than has been approved in Japan. In these countries, 0.29 mg per day of linaclotide is indicated for IBS‐C . Even lower doses of linaclotide, 0.145 mg per day and 0.072 mg per day, have been shown to be effective and safe and have been approved in the United States for the treatment of CC patients .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of interest that North America approved a lower dose of linaclotide for constipated patients than has been approved in Japan. In these countries, 0.29 mg per day of linaclotide is indicated for IBS‐C . Even lower doses of linaclotide, 0.145 mg per day and 0.072 mg per day, have been shown to be effective and safe and have been approved in the United States for the treatment of CC patients .…”
Section: Discussionmentioning
confidence: 99%
“…16 The recommended doses of linaclotide from these studies are 0.29 mg for IBS-C and 0.145 mg for CC. [12][13][14][15][16] By contrast, results [8][9][10] obtained in Japan have been somewhat different. A phase II study of IBS-C patients showed 0.5 mg per day of linaclotide to be the optimal dose.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Linaclotide is an orally active agonist of the guanylate cyclase C receptor (GC‐C), which is approved for the treatment of irritable bowel syndrome with constipation (IBS‐C) . Linaclotide binds with the GC‐C receptor on the luminal aspect of enterocytes and via a number of intracellular signaling cascades lead to increased intracellular cyclic guanosine monophosphate (cGMP).…”
Section: Introductionmentioning
confidence: 99%